P48. Progression of cerebellar involvement in amyotrophic lateral sclerosis as seen by SUIT/ CAT12 voxel-based morphometry and D50 disease modelling. Issue 8 (August 2018) - Batyrbekova, M.; Prell, T.; Stubendorff, B.; Steinbach, R.; Bokemeyer, M.; Mayer, T.; Hartung, V.; Witte, O.W.; Grosskreutz, J.
Abstract : Background: The cerebellum is essential for intact motor function and has an important role in cognitive and neuropsychiatric processes. It is known that the cerebellum is involved in ALS pathology, but the role of gray matter (GM) and white matter (WM) changes is still unclear. Objective: The current study sets out to describe the involvement of the cerebellum with regard to the site of onset, disease phases, degree of disability and disease progression rate in a large cohort of well characterized ALS patients. Methods: T1-weighted MRI of 84 ALS patients and 63 healthy controls were analyzed. Based on these clinical parameters, patients were classified into the subgroups and analyzed to determine changes in the GM and WM. D50 is a new parameter to describe the ALS disease course (D50 = time point when ALSFRS-R drops to 24). Based on D50, ALS disease course can be divided in different disease phases (I-IV), each phase covering half of D50. ALSFRS-R, Δ ALSFRS-R, and D50 were correlated to MRI data of all ALS-patients and patients in phase I and II to show the differences in volume changing patterns. Results: The mean age of the patients was 60 ± 11.49y, m: f was 49:35, ALSFRS-R at MRI was 37 ± 7.29, mean Δ ALSFRS-R was 0.68 ± 0.54, average disease duration was 23 ± 30.08 months, D50 was 38.63 ± 32, 87 months. The patient group included 24 bulbar and 60 limb onsets. 46 patients had a low degree of disability (ALSFRS-R ⩾ 38), 38 were highly impaired (ALSFRS-R < 38). In phase I were 36 patients and in phase II 42. Based on Δ ALSFRS-R, we subgrouped patients in rapid ( Δ ALSFRS-R > 1.5; n = 9) and slow ( Δ ALSFRS-R < 0.5; n = 36). Additionally, the rapid (D50 < 15mo; n = 9) and slow (D50 > 40mo; n = 25) subgroups were categorized based on D50. Late phase and high degree of disability were characterized by pronounced GM reduction in cerebellar regions, whereas WM alterations were localized primarily in brainstem. Rapid progressors show more GM atrophy. Conclusion: Using a spatially unbiased atlas template of the cerebellum and brainstem (SUIT) toolbox and a Computational Anatomy Toolbox for SPM (CAT12) in a large cohort of ALS patients, we were able to indicate that the subtypes demonstrate different patterns of GM-atrophy in cerebellum. These results might be important to understand the pathophysiology of ALS. D50 seems to be more sensitive then Δ ALSFRS-R and could be used as a progression biomarker in combination with Voxel-based Morphometry (VBM). Acknowledgment: This research is supported byBMBF (Bundesministerium für Bildung and Forschung) in the framework of the E-RARE programme (PYRAMID), JPND (OnWebDUALS) of the European Union and theDt. Gesellschaft für Muskelkranke (DGM).